Seed Soaking Time Modulates Germination Traits and Early Vigor of Melon (Cucumis melo L.) - Dede Ardian Syaputra; Vitri Renny Triyanti; Sebrina Shahniza; Sabrina Abdul Razak (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Melon (Cucumis melo L.) is an important horticultural crop whose productivity is strongly influenced by seedquality and early seedling vigor. This study aimed to evaluate the effect of soaking duration on the germinationand early seedling vigor of melon plants (Cucumis melo L.). The research was conducted at MARDI, Malaysia, usinga completely randomized factorial design with five soaking durations (0, 2, 6, 12, and 24 hours) and threereplications. Melon seeds were soaked according to the treatments, then germinated and grown in vermiculite.The observed parameters included root length, root diameter, root volume, and the number of primary andsecondary roots. Data were analyzed using analysis of variance (ANOVA), followed by Duncan's multiple range test.The results showed that soaking duration had a significant effect (P ≤ 0.05) on all measured parameters. Seedswithout soaking (0 hours) exhibited the most optimal root growth, whereas soaking for 24 hours resulted in thelowest values. Excessive soaking caused hypoxic conditions and cellular membrane damage, leading to reducedseed vigor. This study confirms the importance of optimizing soaking duration to enhance germination and earlyseedling vigor in melon